Systematic evaluation of tetra-n-butyl ammonium bromide (TBAB) for carbon dioxide capture employing the clathrate process - Babu, Ponnivalavan; Chin, Weng Inn; Kumar, Rajnish; Linga, Praveen (Industrial & Engineering Chemistry Research, 2014)
Hydrate based gas separation (HBGS) process for the precombustion capture of CO2 from a fuel gas mixture is a novel method being investigated among the carbon capture and sequestration techniques to reduce CO2 emissions. The efficiency of the HGBS process can be improved by using promoters that reduce the formation pressure of mixed gas hydrates. In this study the effect of tetra-n-butyl ammonium bromide (TBAB) was systematically investigated at a constant temperature of 279.2 K and pressure of 6.0 MPa for different TBAB concentrations of 0.3, 1.0, 1.5, 2.0, and 3.0 mol %, respectively. The 0.3 mol % solutions had a relatively longer average induction time of 20.1 min but exhibited the highest total normalized gas uptake of 0.0104 (+/- 0.0004) mol of gas/mol of water and highest separation factor of 41.51 (+/- 6.391). On the other hand, the 1.0 mol % solution had very short average induction time (<0.5 min) and it had the highest hydrate growth rate of 60.8 (+/- 9.89) mol of gas. min(-1).m(-3), with the separation factor of 13.78 (+/- 3.30). Gas solubility measurements and microscopic images of the hydrate formation were also presented to provide greater insights into the effect of TBAB concentration on the gas uptake.